"THE EFFECT OF HABITAT FRAGMENTATION ON THE GENETIC DIVERSITY OF ENDANGERED AMPHIBIAN SPECIES" (International Journal of Food and Nutritional Sciences, 2022)
Species that are already in risk of extinction or very vulnerable face an even greater danger from habitat fragmentation. The impacts of habitat fragmentation are exacerbated for amphibians because of their dependence on particular ecological conditions and limited dispersion capacities. how the loss of habitat affects the genetic diversity of amphibian species that are in danger of extinction. It is possible to learn more about the effects of isolation on amphibian species' gene flow, population structure, and genetic variability by contrasting fragmented populations with more intact, continuous populations. Microsatellite analysis, DNA sequencing, and other molecular genetic techniques allow us to study genetic bottlenecks, inbreeding levels, and genetic divergence in these populations. consequences for amphibian conservation efforts in the long run as a result of changes to genetic diversity brought about by habitat fragmentation. Habitat restoration and wildlife corridor creation are two examples of management tactics that can benefit from this information. how important it is to keep habitats connected so that endangered amphibians can continue to evolve and survive in fragmented environments.